(untitled) (Environment & Health, 2017)
Objective. We performed a cost evaluation of the losses in the economy of Ukraine from premature mortality caused by respiratory diseases. Materials and methods. Social damages connected with the respiratory diseases are considered from the point of view of health losses resulting in reduced quality of life, rising prevalence, and mortality. Economic damages allow the social damages to be presented in numerical expression. Assessment of life cost and loss of the potential years of life (LPYL) are the significant components in these calculations. Mentioned calculations were performed with the help of comparative, medico-statistical, demographic, economic-and-mathematical, structural-and-logical analysis methods of investigation. The official data of the Ministry of Public Health of Ukraine, State Statistics Service and Social Security Fund for 2010- 2015 were used in the study. Results. We assessed the loss of the potential years of life (LPYL) as a result of premature mortality according to the classes of diseases connected with the respiratory system. Obtained data show that 36.2% cases of deaths of pneumonia, 35.6% deaths of malignant tumors of tracheal, bronchi, and lungs, 10.4% cases of deaths of chronic diseases of lower respiratory tracts make up a significant part in a total number of the loss of the potential years of life. By all selected diseases, at one cases of death, 8.87 years of potential life is lost per year. Obtained calculations of the quantitative assessments of the loss of the potential years of life with the application of the feedback index of the use of human capital as a cost evaluation of human life (it made up 46413 UAH, or 2124, USD in 2015) allowed to get a sum of economic losses – 11.4 billions UAH, or 523.8 millions USD. While using the element-by-element approach to the data of 2015, the economic losses of the state because of premature mortality of the respiratory diseases made up 1.2% GDP, or 24.03 billions UAH.